Differences in the Gut Microbiota Establishment and Metabolome Characteristics Between Low- and Normal-Birth-Weight Piglets During Early-Life - Li, Na; Huang, Shimeng; Jiang, Lili; Wang, Wei; Li, Tiantian; Zuo, Bin; Li, Zhen; Wang, Junjun (Frontiers in Microbiology, 2018)
Low-birth-weight (LBW) piglets are at high risk for postnatal growth failure, mortality, and metabolic disorders later in life. Early-life microbial exposure is a potentially effective intervention strategy for modulating the health and metabolism of the host. Yet it has not been well elucidated whether the gut microbiota development in LBW piglets is different from their normal littermates, and its possible association with metabolite profiles. In the current study, 16S rRNA gene sequencing and metabolomics was used to investigate differences in the fecal microbiota and metabolites between LBW and normal piglets during early life, including day 3 (D3), 7 (D7), 14 (D14), 21 (D21, before weaning) and 35 (D35) after birth. Compared to their normal littermates, LBW piglets harbored lower proportions of Faecalibacterium on D3, Flavonifractor on D7, Lactobacillus, Streptococcus and Prevotella on D21, as well as Howardella on D21 and D35. However, the abundances of Campylobacter on D7 and D21, Prevotella on D14 and D35, Oscillibacter and Moryella on D14 and D21 and Bacteroides on D21 were significantly higher in LBW piglets than those in normal piglets. The results of the metabolomics analysis suggested that LBW significantly affected fecal metabolites involved in fatty acid metabolism (e.g., linoleic acid, α-linolenic acid and arachidonic acid), amino acid metabolism (e.g., valine, phenylalanine and glutamic acid), as well as bile acid biosynthesis (e.g., glycocholic acid, 25-hydroxycholesterol and chenodeoxycholic acid). Spearman correlation analysis revealed a significant negative association between Camplylobacter and N1-acetylspermine on D7, between Moryella and linoleic acid on D14, between Prevotella and chenodeoxycholic acid on D21, and between Howardella and phenylalanine on D35, respectively. Collectively, LBW piglets have a different gut bacterial community structure compared to NBW piglets during early life, especially from 7 to 21 days of age. Also, a distinctive metabolic status in LBW piglets might be partly associated with the altered intestinal microbiota. These findings may further elucidate factors potentially associated with the impaired growth and development of LBW piglets and facilitate the development of nutritional interventions.